2012
DOI: 10.1523/jneurosci.5877-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Band Oscillations in the Primary Somatosensory Cortex—A Direct and Obligatory Correlate of Subjective Pain Intensity

Abstract: Electroencephalographic gamma band oscillations (GBOs) induced over the human primary somatosensory cortex (SI) by nociceptive stimuli have been hypothesized to reflect cortical processing involved directly in pain perception, because their magnitude correlates with pain intensity. However, as stimuli perceived as more painful are also more salient, an alternative interpretation of this correlation isthatGBOsreflectunspecificstimulus-triggeredattentionalprocessing.Infact,thisissuggestedbyrecentobservationsthat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
284
3
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(335 citation statements)
references
References 48 publications
27
284
3
11
Order By: Relevance
“…Explaining this issue, it is worth mentioning that the average of the VAS pain ratings across all recordings and all subjects was 5.5 at the i-DUST 2016 hospital and 1.5 at LSBB, suggesting that despite the efforts to keep the experiment conditions equal, the subjects experienced more pain in the hospital facility than in LSBB. We might therefore hypothesize that the lower ratios in LSBB are caused by the lower pain experience in comparison with ICORD, which would in turn yield lower gamma band activity in LSBB as the strength of gamma band oscillations has been shown to correlate well with the intensity of the perceived pain [10]. However, since only a small number of subjects (two) were included for the heat task, caution must be exercised in interpreting the results pertaining to this task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Explaining this issue, it is worth mentioning that the average of the VAS pain ratings across all recordings and all subjects was 5.5 at the i-DUST 2016 hospital and 1.5 at LSBB, suggesting that despite the efforts to keep the experiment conditions equal, the subjects experienced more pain in the hospital facility than in LSBB. We might therefore hypothesize that the lower ratios in LSBB are caused by the lower pain experience in comparison with ICORD, which would in turn yield lower gamma band activity in LSBB as the strength of gamma band oscillations has been shown to correlate well with the intensity of the perceived pain [10]. However, since only a small number of subjects (two) were included for the heat task, caution must be exercised in interpreting the results pertaining to this task.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the disruptive effects of electrical interference and movement (i.e. noise), depending on the neuronal activity of interest, EEG is often band-pass filtered at different frequencies from 0.5 to 100 Hz and is then studied in terms of activity across different frequency bands; including (0-4 Hz), (4)(5)(6)(7), (8)(9)(10)(11)(12) Hz), (12-30 Hz), and (30-100 Hz). Clinically, EEG frequencies are most often studied from 0.5 to 30 Hz with the gamma ( ) band being ignored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,19,23,24 Functionally, gamma oscillations in neuronal networks bind neurons into a common temporal regime during higher brain functions like motor behavior, sensory perception, or memory formation. 7,[25][26][27][28] The synchronizing effect of gamma oscillations permits the coordinated activation of defined sets of neurons, which constitute functional ensemblesthe putative information-carrying multicellular subsets of neuronal networks. 9,11,29 Moreover, the precise timing of action potentials is central for use-dependent synaptic plasticity and, thus, supports learning and memory formation.…”
Section: Gamma Oscillations and Cortical Information Processingmentioning
confidence: 99%
“…Electroencephalography, in contrast, is a non-invasive neurophysiological method that records the electrical activity of the brain at the scalp, largely from superficial regions, such as the somatosensory cortex, because voltage changes dissipate from deeper subcortical structures over a certain distance. It is possible to observe event-related changes in the EEG traces following certain stimuli, including noxious laser, pinprick and heel lance (Zhang et al 2012;Fabrizi et al 2013;Iannetti et al 2013). Recently, studies have identified an event-related potential in newborn infants and infants up to 1 year old, which is specific to noxious stimulation (Slater et al 2010b,c;Fabrizi et al 2011;Verriotis et al 2015).…”
Section: Infant Pain and The Cerebral Cortexmentioning
confidence: 99%